2016
DOI: 10.1080/00207179.2016.1209565
|View full text |Cite
|
Sign up to set email alerts
|

Identification and control of electro-mechanical systems using state-dependent parameter estimation

Abstract: International audienceThis paper addresses the important topic of electro-mechanical systems identification with an application in robotics. The standard inverse dynamic identification model with least squares (IDIM-LS) method of identifying models for robotic systems is based on the use of a continuous-time inverse dynamic model whose parameters are identified from experimental data by linear LS estimation. The paper describes a new alternative but related approach that exploits the state-dependent parameter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 40 publications
0
30
0
Order By: Relevance
“…The parameters of SDP models are functionally dependent on measured variables, such as joint angles and velocities in the case of manipulators. Such models have been successfully used for control of a KOMATSU hydraulic excavator [17], while [18] further demonstrates the advantages of the SDP approach, in comparison to IDIM-LS methods.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…The parameters of SDP models are functionally dependent on measured variables, such as joint angles and velocities in the case of manipulators. Such models have been successfully used for control of a KOMATSU hydraulic excavator [17], while [18] further demonstrates the advantages of the SDP approach, in comparison to IDIM-LS methods.…”
Section: Introductionmentioning
confidence: 92%
“…However, the present article instead focuses on the identification of a relatively straightforward SDP model. In contrast to earlier SDP control of the same device [2], a new model structure is identified, one that provides estimates of the dead-zone and angular velocity saturation, in a similar manner to the friction analysis of Janot et al [18]. This model facilitates use of an Inverse Dead-Zone (IDZ) [21] controller, which is combined with conventional Proportional-Integral-Plus (PIP) methods [22].…”
Section: Introductionmentioning
confidence: 99%
“…Identification methods for robotic systems include, for example, maximum likelihood and inverse dynamic identification model with least squares (IDIM-LS) [47]. Refined Instrumental Variable (RIV) algorithms are also used, sometimes in combination with inverse dynamic [48,49] or SDP [2] models. However, in contrast to earlier SDP research for the same device [2], an improved model structure is identified here.…”
Section: Robot Dynamicsmentioning
confidence: 99%
“…In Janot et al (2017), authors propose a statistical identification procedure named state dependant parameter (SDP) estimation. The method allows to identify and estimate non-linearities in the dynamic system.…”
Section: Model Parameter Estimationmentioning
confidence: 99%